Cross-racial envy and underinvestment in South Africa - Daniel Haile; Abdolkarim Sadrieh; Harrie A. A. Verbon (Center for Economic Studies and ifo Institute (CESifo), 2006)
Trust games are employed to investigate the effect of heterogeneity in income and race on cooperation in South Africa. The amount of socio-economic information available to the subjects about their counterparts is varied. No significant behavioural differences are observed, when no such information is provided. However, when the information is available, it significantly affects individual trust behaviour. The low income subjects from both racial groups invest significantly less in partnerships with the high income subjects of the other racial group than in any other partnership. We attribute this behaviour to cross-racial envy, which on aggregate may lead to substantial underinvestment in the economy.
Keywords: J15; C91; 330; trust game; ethnic diversity; income inequality; cooperation; Kooperation; Vertrauen; Ethnische Beziehungen; Einkommensverteilung; Investition; Experiment; Spieltheorie; Theorie; Südafrika